Future of Chondroprotectors in the Treatment of Degenerative Processes of Connective Tissue - Stanislav Sukhikh; Olga Babich; Alexander Prosekov; Nikolai Patyukov; Svetlana Ivanova (MDPI AG, 2020)
Osteoarthritis is one of the most common diseases of the connective tissue of the elderly. It was found that most epidemiological studies used the Kellgren and Lawrence system for classification of osteoarthritis, which indicates one of the 5 degrees (0-4) of osteoarthritis in various joints according to the radiographic atlas. It has been proven that chondroprotectors are represented by the following active substances: chondroitin sulfate, glucosamine sulfate or hydrochloride, hyaluronic acid, glycosaminoglycans, extraction preparations from animal or plant raw materials. The sources of raw materials for the manufacture of combined chondroprotectors are known, methods for their preparation and use are described. The main drugs on the chondroprotective market are presented. The effectiveness of their use for the treatment of osteoarthritis has been proven. It was found that preparations containing chondroitin sulfate have anti-inflammatory activity, affecting mainly the cellular component of inflammation, stimulate the synthesis of hyaluronic acid and proteoglycans. Methods of treating osteoarthritis using cell therapy (the use of readily available, highly proliferative, and multipotent mesenchymal stromal cells) are presented.